Determinants of timely initiation of breastfeeding among mothers in Goba Woreda, South East Ethiopia: A cross sectional study - Belachew Tefera; Gerbaba Mulusew; Setegn Tesfaye (BMC, 2011)
Abstract Background Although breastfeeding is universal in Ethiopia, ranges of regional differences in timely initiation of breastfeeding have been documented. Initiation of breastfeeding is highly bound to cultural factors that may either enhance or inhibit the optimal practices. The government of Ethiopia developed National Infant and Young Child Feeding Guideline in 2004 and behavior change communications on breast feeding have been going on since then. However, there is a little information on the practice of timely initiation of breast feeding and factors that predict these practices after the implementation of the national guideline. The objective of this study is to determine the prevalence and determinant factors of timely initiation of breastfeeding among mothers in Bale Goba District, South East Ethiopia. Methods A community based cross sectional study was carried out from February to March 2010 using both quantitative and qualitative methods of data collection. A total of 608 mother infant pairs were selected using simple random sampling method and key informants for the in-depth interview were selected conveniently. Descriptive statistics, bivariate analysis and multivariable logistic regression analyses were employed to identify factors associated with timely initiation of breast feeding. Results The prevalence of timely initiation of breastfeeding was 52.4%. Bivariate analysis showed that attendance of formal education, being urban resident, institutional delivery and postnatal counseling on breast feeding were significantly associated with timely initiation of breastfeeding (P < 0.05). After adjust sting for other factors on the multivariable logistic model, being in the urban area [AOR: 4.1 (95%C.I: 2.31-7.30)] and getting postnatal counseling [AOR: 2.7(1.86-3.94)] were independent predictors of timely initiation of breastfeeding. Conclusions The practice of timely initiation of breast feeding is low as nearly half the mothers did not start breastfeeding with one hour after delivery. The results suggest that breast feeding behavior change communication especially during the post natal period is critical in promoting optimal practice in the initiation of breast feeding. Rural mothers need special attention as they are distant from various information sources.